The carboniferous flora of northeastern thailand : Additional documentation from the Na duang-na klang basin - Jean Pierre Laveine (2018)
Carboniferous palaeobotanical data recorded lately from the Na Duang-Na Klang basin in northeastern Thailand provide additional documentation on the Carboniferous flora reported from this basin during the last decades. A new lycopsid species, Lepidodendron timsuwanii, which exhibits minute leaf cushions showing round to slightly ovate leaf scars and elongate infrafoliar parichnos, is described. Beyond their interest from a taxonomical viewpoint these palaeobotanical remains, essentially of Euramerican aspect, confirm the key role of these floras in the debate concerning the palaeogeography of East Asia and Southeast Asia during Carboniferous time.